Substantiation and fundamentals of medico-psychological escort in the child neurosurgery sphere - Dukhovskyy, Oleksandr (ScienceRise: Medical Science, 2017)
Aim: Comprehensive study of the features of emotional disorders in the parents of a child of the first year of life with severe craniocerebral trauma. Materials and methods. To achieve this aim, in compliance with the principles of bioethics and medical deontology was conducted a comprehensive clinical-anamnestic, clinical-psychological and psychodiagnostic examination of 137 families (mother and father) of children of the first year of life who received a craniocerebral trauma. All the examined families were full (mother and father), the average age of their parents was 27.0 ± 3.0 years. The main group consisted of 97 families who took part in the program of medical and psychological support using psycho education. Control group - 40 families who did not receive psychological support. The following survey methods were used in the study: clinical and anamnestic; clinical and psychological; psychodiagnostic using a questionnaire of nervous-psychic stress, clinical scale of anxiety and depression of Hamilton, adapted to MKH-10; scale of situational and personal anxiety Ch.D. Spielberger, methods of studying the styles of stress-breaking behavior "Methods of coping", methodology "Determination of ways to resolve conflicts" by K. Thomas in adaptation by N.V. Grishina. Results of the research. The child’s illness is a traumatic situation for all parents, which leads to the development of anxiety-depressive reactions and conditions. Distributed anxiety-depressive, astheno-depressive, depressive-apatitic and dysphoric variants of emotional disorders in the parents of infants with severe craniocerebral trauma and described their clinical features. For parents of infants with severe craniocerebral trauma are characterized as ones with high levels of emotional stress, a sharp increase of negative emotions, a feeling of anxiety, depressive manifestations. The obtained results allowed to substantiate expediency of medical-psychological support of the family with the first year child with severe craniocerebral trauma, which includes methods of differentiated psychotherapy and psycho-educational programs. Conclusions The structure of psycho-emotional disorders in the parents of infants with severe craniocerebral trauma is represented by anxiety-depressive (40.9%), asthenoid-depressive (22.5%), depression-apathy (20.5%) and dysphoric (16.1%) variants. The efficiency of the system of medical and psychological support of the family with the first year child with severe craniocerebral trauma, which includes methods of differentiated psychotherapy and psycho-educational programs is proved